2010
DOI: 10.1183/09031936.00034310
|View full text |Cite
|
Sign up to set email alerts
|

Regional ventilation distribution in the first 6 months of life

Abstract: Electrical impedance tomography (EIT) has been used to study regional ventilation distribution in neonatal and paediatric lung disease; however, little information has been obtained in healthy newborns and infants.Data on regional ventilation distribution and regional filling characteristics were obtained using EIT in the neonatal period, at 3 and 6 months of age, in spontaneously breathing infants during non-rapid eye movement sleep. Regional ventilation distribution was described using regional end-expirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 32 publications
8
33
0
2
Order By: Relevance
“…In healthy preterm infants, the posterior (dependent) lung filled significantly earlier than the anterior lung in the supine position. Similar time-course characteristics were also found in supine in healthy newborns (5). This finding is consistent with the lung model proposed by Milic-Emili et al (31), which showed that the rate of volume change during the initial phase of tidal volume ventilation was greatest in the dependent lung.…”
Section: Effect Of Position On Regional Lung Fillingsupporting
confidence: 85%
See 2 more Smart Citations
“…In healthy preterm infants, the posterior (dependent) lung filled significantly earlier than the anterior lung in the supine position. Similar time-course characteristics were also found in supine in healthy newborns (5). This finding is consistent with the lung model proposed by Milic-Emili et al (31), which showed that the rate of volume change during the initial phase of tidal volume ventilation was greatest in the dependent lung.…”
Section: Effect Of Position On Regional Lung Fillingsupporting
confidence: 85%
“…Similar results were also found by our study group in healthy term newborns during non-rapid eye movement sleep (5).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…[24][25][26] However, it should be remembered that mucociliary clearance is predominant in the dependent lung areas of semi-sitting infants, as in adults, being stimulated by regional ventilation. [27][28][29] No wonder that conventional CPT gives poor results and is poorly tolerated, with side effects such as esophageal reflux, tachypnea, tachycardia, hypoxemia, rib fracture, and severe central nervous system complications, especially in newborns. [30][31][32][33][34] The 2012 Cochrane review showed no significant benefit from conventional CPT on clinical score or hospital stay, and conventional CPT in acute viral bronchiolitis is no longer recommended.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…At the 2010 ERS Congress a number of research groups reported data from alternative techniques to quantify inhomogeneity. PHAM et al [107] reported EIT recordings in spontaneously breathing term infants measured soon after birth and again at 3 and 6 months SCIENTIFIC ASSEMBLY UPDATE: PAEDIATRICS E. EBER ET AL.…”
Section: Paediatric Respiratory Physiologymentioning
confidence: 99%